Brainstorming about the Future of Solid Earth Sciences in Canada - Sylvester, Paul; Hall, Jeremy; Bleeker, Wouter (Geoscience Canada, 2005)
SUMMARY This article is a synopsis of an informal meeting that was convened in Montreal last May to discuss strategic planning for the "Solid Earth Sciences" in Canada. Five possible approaches for developing a new research program are discussed and the lessons from LITHOPROBE are reviewed. This is followed by a brief overview of existing and emerging Solid Earth Science projects that are focussed on the Continental, Far North, Marine, and Planetary realms. There is also a section on future directions of federal and provincial geological surveys. Finally, at least two workshops are proposed to define and flesh out research themes, and identify funding pathways. One should deal with research in continental geology, perhaps using the "Taking the Pulse of Planet Earth" proposal as a starting point. A second should explore research opportunities for solid earth scientists in planetary science and attempt to develop funding links with the Canadian Space Agency.